Morphometric and histological analysis of chronic end metritis in women of reproductive age - Rakhmonova Shakhnoza; Nurov Akobir; Ashirmatov Sherali (Research Parks Publishing LLC, 2020)
Despite the high achievements of modern morphology, some issues related to the pathogenesis of infertility and habitual miscarriage remain poorly understood, which determines the possibility of further research. It is known that endometrial steroid receptors play an important role in the process of pregnancy initiation and continuation Meanwhile, in relation to unclear infertility, as well as chronic end metritis, as the causes of reproductive pathology, endometrial receptors for estrogen and progesterone have been studied only to a small extent, which, of course, requires supplementation.